Benzoxazine/amine-based polymer networks featuring stress-relaxation and reprocessability - Pursche, Lea; Wolf, Adrian; Urbaniak, Tobias; Koschek, Katharina (Frontiers in Soft Matter, 2023)
Amines as additives in benzoxazines are known to beneficially affect the polymerization temperature and furthermore to allow for partially reversible reaction steps yielding however a non-dynamic polybenzoxazine network. This contribution proves that the polymerization behavior of a two-component polymer of the polyetheramine Jeffamine® ED-600 and a bisphenol-A-based benzoxazine features stress-relaxation and reprocessability usually known from vitrimers. With the aim to gain a deeper understanding of the material properties of this system and the corresponding polymer structure, the reaction mechanism of a monofunctional benzoxazine and monoamine model system was studied revealing at first primary, and then secondary amine induced opening of oxazine rings, leading at first to linear polymer chains and then to covalently crosslinked networks. Both consist of repeated phenolic benzoxazine/amine motifs with permanently incorporated polyetheramine chains that do not impact the mechanical properties, compared to pure polybenzoxazine. Thermal, spectroscopic, and extraction analyses show that the addition of Jeffamine® reduces the polymerization temperature and introduces material properties such as reprocessability at the same time. Stress-relaxation measurements support the assumption that the reprocessability point to vitrimer-like molecular processes. The material shows rapid stress-relaxation of up to 11 s, a corresponding bond-exchange activation energy of 146 kJ/mol, and a topology freezing temperature of 97 °C.